Resíduos da flotação de galena e areia de fundição, reaproveitados como substitutos de recursos naturais para produção de cerâmicas ambientalmente limpas e seguras - Correia, Renata Alves Monteiro (2019)
In Brazil, for fifty-eight years, lead and silver were extracted on a large scale from Galena and Cerusite mining. The waste from this activity left profound environmental and social impacts in the city of Adrianópolis. The main objective of this work is to evaluate the effects of the partial substitution of clay for flotation residue of galena and foundry sand for the production of sustainable ceramics. In this research 20 composition were sintered at 900-120° and their properties were studied. Their mechanical characteristics were analyzed using flexural strength test, water absorption, density, linear shrinkage. The studies of the physicochemical properties were performed using high technology such as, XRF, XRD, SEM/EDS to characterize the ceramic developed. For the environmental analysis of the ceramic with the best flexural strength, heavy metals leaching analysis was performed as established in ABNT NBR 10004: 1987. All the ceramics presented bending resistance results higher than the values established in the national standards (>1,5MPa).The best results of the mechanical resistance module can be observed in the composition ceramic containing with 7% of the flotation residue and 10% the foundry sand and showed the resistance mechanical 3.89MPa to 10.8MPa. The results of the retraction analysis demonstrate that the flotation residue interacts positively with respect to avoiding the reduction of the size of the ceramic bodies, conferring excellent retraction results when compared to the ceramic bodies without the introduction of the flotation residue. In the composition containing 7% of flotation residue and 10% foundry sand, the measured retraction varied from 0.05% to 5.6%, while in the test specimens without the residue the results ranged from 2.97% to 6.65%. Flotation residues also exert a positive influence on water absorption indices, the absorption reduction reaching up to 65% at 1250 ° C when compared to traces without flotation addition. The density of the ceramic bodies did not undergo significant changes with the introduction of the flotation residues when compared to the traces without the residue, being the result about insignificant density in the different firing temperatures. For environmental analysis of the ceramics, leaching and solubilization analyzes of potentially toxic metals were performed according to the methodology and limits established by ABNT NBR 10004: 2004 and 10005: 2004. The leaching analysis showed that there is no environmental risk in the use these residues to fabrication new materials ceramics. According to the classification established by ABNT NBR 15270-1: 2005 all ceramics sintered up to 1200 ° C can be classified as ceramic blocks as well as ceramics from 1 up to 11 sintered up to 1250 ° C. In order to classify ceramics from 12 to 20 sintered at 1250 ° C, the limits of water absorption and the mechanical strength module of ABNT NBR 13828 were used, so it's possible this ceramics could be classified as porcelain, however, it is necessary to carry out additional analysis that wasn't in this research.